Variant analysis of financial and energy efficiency of the heat recovery system and domestic hot water preparation for a single-family building: The case of Poland. (15th April 2023) - Piotrowska, Beata; Słyś, Daniel
Abstract: Significant amounts of waste heat are deposited in wastewater, which can be used e.g. for heating domestic water. The aim of the paper was to analyze the efficiency of energy recovery from gray water using a new horizontal heat exchanger in the form of a linear drainage equipped with a wavy middle wall. The experimental research consisted of the analysis of efficiency of the device prototype, and then the calculation of energy savings for the preparation of domestic hot water for 81 test cases. Installations cooperating with an electric and gas water heater were analyzed. A Life Cycle Cost analysis was carried out for the financial effectiveness of a conventional installation and an installation equipped with a heat exchanger for a family of 3. Research have shown that the new heat exchanger reduces energy consumption for hot water preparation by an average of 22–31%. It was established that when using an electric water heater, the investment costs pay back in the period of 4–9 years, and in the case of a gas heater, at least 12 years. The sensitivity analysis showed that an increase in energy prices can significantly shorten the payback period, to 6 years for a gas heater and 2 years for an electric heater. Research has shown that the new heat exchanger can significantly reduce the amount of energy needed to prepare domestic hot water. The research results can be useful for researchers, designers and potential users of heat recovery systems. Graphical abstract: Image 1 Highlights: The new horizontal heat exchanger was examined in laboratory conditions. The shower length does not affect the efficiency of the heat exchanger. The lowest costs of preparing hot water were obtained using a gas heater. The investment is most profitable when using an electric water heater.